Consumer Anthropomorphism and Happiness: Analysis of the Brand Authenticity Effect - Mehdi Khademi Gerashi; Setare Mohammadian (‫مدیریت بازرگانی)
Objective The human mind, with the help of anthropomorphism, makes every unknown thing that it knows less like the most familiar thing that it knows the most, i.e. a human being (himself). The process of anthropomorphism refers to the special desire of humans to attribute human characteristics to non-human beings, which can provide a basis for greater satisfaction. Given that people naturally tend to attribute human characteristics to beings, objects, and phenomena, and many researchers consider this tendency an essential tool for comprehending factors beyond human nature, it can serve as a foundation for enhancing customer satisfaction. This study aims to investigate the impact of brand anthropomorphism on consumer happiness, considering both emotional and cognitive aspects, and to examine the mediating role of brand authenticity across four dimensions: continuity, correctness, symbolism, and credibility.